OECD Imports : Diversification of Suppliers and Quality Search - Cadot, Olivier; Carrere, Celine; Strauss-Kahn, Vanessa (2012)
This paper explores the evolution of OECD imports over time, measuring their concentration across origin countries at the product level. The authors find evidence of diversification followed, in the very last years of the sample period (post-2000), by a slight re-concentration. This re-concentration is entirely explained by the growing importance of Chinese products in OECD imports. They also find evidence of relatively more volatile concentration levels for goods with high quality heterogeneity, with temporary phases of re-concentration on goods with higher unit values. Both findings are consistent with a simple model of adverse selection and quality screening by OECD buyers predicting that diversification happens by "bouts" rather than continuously, with temporary re-concentration on higher-quality suppliers.